Optimization of Extrusion on Blend Flour Composed of Corn, Millet and Soybean - Semasaka, Carine; Kong, Xiangzhen; Hua, Yufei (Pakistan Journal of Nutrition, 2010)
Formulations made of blends of 44% corn flour, 36% millet flour and 20% soybean flour were performed using DPSv 11.50 software. The blends were extruded in Twin screw extruder and orthogonal array L9 (34) was used to evaluate the optimized extrusion conditions. The explanatory variables used were temperature (for the feeding, mixing, cooking and die zones), Rolling speed, feeding speed and moisture content of the samples. The response variables were bulk density, WAI, WSI, pasting properties, thermal analysis, swelling power and the color of the extrudates. The better factors and levels showed that the temperature 80, 110, 140 and 170oC, rolling speed of 110 rpm, feeding speed of 37 g/min and moisture content varies from 25-30% are the best for the extrusion of that formulation.